2022
DOI: 10.3389/fimmu.2021.801164
|View full text |Cite
|
Sign up to set email alerts
|

B Cells Adapt Their Nuclear Morphology to Organize the Immune Synapse and Facilitate Antigen Extraction

Abstract: Upon interaction with immobilized antigens, B cells form an immune synapse where actin remodeling and re-positioning of the microtubule-organizing center (MTOC) together with lysosomes can facilitate antigen extraction. B cells have restricted cytoplasmic space, mainly occupied by a large nucleus, yet the role of nuclear morphology in the formation of the immune synapse has not been addressed. Here we show that upon activation, B cells re-orientate and adapt the size of their nuclear groove facing the immune s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 62 publications
1
5
0
Order By: Relevance
“…We observed that this process is characterized by two classes of events: a first phase (in the first 3.5 min), where F-actin is strongly polymerized at the site of contact, leading to antigen accumulation and production of DAG as a result of BCR signaling, and a second phase during which the centrosome is reoriented toward the immune synapse together with the Golgi apparatus and lysosomes while the nucleus undergoes a rotation followed by backward transport. The timescales we found for late polarization events are shorter than the ones measured for B cells in other systems (e.g., centrosome polarized in 30 min [ Yuseff et al, 2011 ], nucleus fully polarized in 30 min [ Ulloa et al, 2022 ], lysosomes maximally clustered in 40 min [ Spillane and Tolar, 2018 ]) and much closer to results found in T cells ( Gawden-Bone et al, 2018 ; Yi et al, 2013 ; Hooikaas et al, 2020 ), possibly due to the properties of the substrate that we used for antigen presentation. We found that F-actin polymerization is only needed for the first phase, in contrast to microtubules that not only control centrosome and organelle repositioning, but further maintain a unique polarity axis by restricting actin nucleation to the immune synapse.…”
Section: Discussionsupporting
confidence: 66%
“…We observed that this process is characterized by two classes of events: a first phase (in the first 3.5 min), where F-actin is strongly polymerized at the site of contact, leading to antigen accumulation and production of DAG as a result of BCR signaling, and a second phase during which the centrosome is reoriented toward the immune synapse together with the Golgi apparatus and lysosomes while the nucleus undergoes a rotation followed by backward transport. The timescales we found for late polarization events are shorter than the ones measured for B cells in other systems (e.g., centrosome polarized in 30 min [ Yuseff et al, 2011 ], nucleus fully polarized in 30 min [ Ulloa et al, 2022 ], lysosomes maximally clustered in 40 min [ Spillane and Tolar, 2018 ]) and much closer to results found in T cells ( Gawden-Bone et al, 2018 ; Yi et al, 2013 ; Hooikaas et al, 2020 ), possibly due to the properties of the substrate that we used for antigen presentation. We found that F-actin polymerization is only needed for the first phase, in contrast to microtubules that not only control centrosome and organelle repositioning, but further maintain a unique polarity axis by restricting actin nucleation to the immune synapse.…”
Section: Discussionsupporting
confidence: 66%
“…We observed that Vti1b was specifically polarised to the IS upon BCR activation ( Figure 3 ). It has been widely reported that lymphocytes polarise the endocytic/exocytic machinery, as well as other organelles, such as the Golgi apparatus, to the IS ( del Valle Batalla et al, 2018 ; Duchez et al, 2011 ; Ulloa et al, 2022 ; Yuseff et al, 2011 ). Thus, it was not unexpected that Vti1b, which mainly resides in the Golgi and lysosomes, would polarise to the IS.…”
Section: Discussionmentioning
confidence: 99%
“…The distribution of lysosomes within Z sections was previously described [ 37 ]. Values of lysosomes were calculated by measuring their mean fluorescence intensity (MFI) in the cell at each z-slice (0.2 µm) from the immune synapse (defined by the contact area on antigen coated dishes) to the top of the cell.…”
Section: Methodsmentioning
confidence: 99%